Sporting Nationalism in Olympic Badminton: Olympic Badminton in Sociological Literature — Constructing Nationalism, Collective Identity, and Emotional Mobilization - Yoga Adil Anugrah Zamasi; Andesta Lingling Ambarita; Wilson Situmorang; Muhammad Nurdzaky Alfatih; Amos Bastanta Gurusinga; Michael Christiano Sitinjak; Nurkadri Nurkadri (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2026)
Objectives: This systematic review examines the sociological literature on sporting nationalism as constructed through Olympic badminton, focusing on how nationalism, collective identity, and emotional mobilization are discursively produced and sustained within international badminton competition. The review integrates interdisciplinary scholarship from the sociology of sport, nationalism studies, media discourse analysis, and social psychology to identify dominant theoretical trends and research gaps regarding badminton as a vehicle for nation-building narratives. Methods: The study followed PRISMA 2020 guidelines through comprehensive searches in Scopus, Web of Science, SPORTDiscus, PsycINFO, and Sociology Source Ultimate for publications published between January 2000 and December 2025. Search terms included combinations of “badminton,” “Olympic,” “nationalism,” “collective identity,” “emotional mobilization,” and “sport sociology.” After screening and eligibility assessment, 42 studies were included in the qualitative synthesis. Data extraction was independently conducted by two reviewers, and thematic analysis generated four principal domains: media narratives of nationalism, collective identity formation, emotional mobilization, and geopolitical rivalry through badminton diplomacy. Results: Findings indicate that Olympic badminton functions as a powerful arena for nationalist expression, particularly in Asian countries such as China, Indonesia, Malaysia, South Korea, Japan, and India, where badminton holds strong cultural significance. Media discourse emerged as the central mechanism amplifying nationalist sentiment, while live and mediated spectatorship generated collective emotional experiences that reinforced imagined national communities. Conclusion: The review also highlights the complex negotiation of ethnic and diasporic identities, especially among ethnic Chinese athletes in Malaysia and Indonesia. Overall, Olympic badminton represents a significant yet underexplored domain within the sociology of sporting nationalism. Future research should adopt longitudinal and comparative approaches while integrating postcolonial, decolonial, and digital ethnographic perspectives to better understand evolving forms of nationalist expression in contemporary Olympic sport.